A comprehensive metabolomic and lipidomic analysis reveals the effect of temperature on flounder (Paralichthys olivaceus). (February 2022) - Liu, Guilin; Wang, Hongxiang; Lv, Zhihua; Tang, Xiaoqian; Yu, Mingming
Abstract: Temperature is a considerable stressor in aquatic environments. The objective of this study was to investigate the changes in endogenous compounds of flounder ( Paralichthys olivaceus ) at different temperatures based on a holistic metabolomic and lipidomic analysis. Accordingly, this study involved reversed-phase chromatography and hydrophilic interaction chromatography coupled with a mass spectrometry detection platform, and using a new database, and multivariate statistical analysis. In total, 954 unique masses were obtained, including 495 metabolites and 459 lipids, and 53 qualified differential metabolites were filtered. Specifically, among the highlighted biomarkers, 2′-Hydroxy-5′-methylacetophenone and FFA (17:1) were the metabolites and lipids with the largest Log2 FC, respectively. In addition, 18-Hydroxycorticosterone showed the greatest downregulation. Hypoxia-inducible factor 1 signaling pathway, biosynthesis of amino acids, glycerophospholipid metabolism, and choline metabolism in cancer were enriched and noteworthy metabolic pathways, which were closely related. Overall, this study provides potential serum biomarkers and metabolic pathways for flounder as well as a reference for further studies on the physiological functions of flounder under different stressors. Highlights: Flounder serum metabolic characteristics as well as metabolic pathways were obtained. Metabolites and lipids changed significantly at 20 °C compared with 10 °C. All differentially abundant lipids were up-regulated.